Identification of Pyroptosis-Related Gene Signatures and Construction of the Risk Model to Predict BCR in Prostate Cancer - Wang, Miaomiao; Xia, Haoran; Yan, Qiuxia; Liu, Wen; Liu, Ming; Wang, Xuan (Frontiers in Molecular Biosciences, 2022)
Prostate cancer is one of the most common malignant tumors in men. Pyroptosis is related to tumor immune infiltration and tumor microenvironment (TME) and has been confirmed to be related to the progression of a variety of tumors. However, the relationship between prostate cancer and Pyroptosis, as well as TME and tumor immune infiltration has not been discussed yet. We obtained the RNA-seq data of prostate cancer from TCGA and GEO databases, and analyzed the differential expression of pyroptosis related genes in prostate cancer samples, then divided them into two groups according to the expression level of pyroptosis-related genes. Further verified the relationship between pyroptosis subtypes and TME of prostate cancer, and identified the differential expression genes (EDGs) in the two subtypes. Explored the relationship between the differential genes and the clinicopathological was explored, and KEGG GO enrichment analysis was conducted. It was found that most of the differential genes between the two groups were enriched in immune-related pathways. Then we randomly divide the patients into t training and testing sets, performed Lasso and multicox progression analysis on DEGs, selected the most likely 8 genes as the prognostic signature, and use the 8 genes calculate the risk score, then separated entire cohort into high-risk and low-risk groups, and the prognosis between two risk groups and the 1-, 3-, 5-year ROC curve of Biochemical relapse (BCR) were verified in training, testing, and entire cohort respectively. TME, CSC index and mutation in different risk groups, as well as drug susceptibility were also discussed.